1987
DOI: 10.1002/jemt.1060060109
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of some mechanical properties of embedding resins with their behaviour in microtomy

Abstract: The technology of ultramicrotomy is now well established, but the properties of the resin that determine the different forces needed to generate a section have been neglected, although this process could introduce artefacts in the thin sections. We have investigated the principal resin dependent factors involved in the sectioning process and determined the related mechanical properties. Tensile experiments have given the best correlation with the sectioning quality of the resin: the elastic (Young's) modulus v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
5

Year Published

1997
1997
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 45 publications
1
37
0
5
Order By: Relevance
“…With this new resin, the effects of surface relief on imaging were strongly enhanced (Kellenberger et al, 1986) and convincingly revealed the origin of the blurring. We could demonstrate a strong deformation of the resin surface in the near neighborhood of biological material, which was in full agreement with the physics of cleavage mentioned above and discussed elsewhere (Acetarin et al, 1987). Through cleavage, all matter of the section surface is submitted to strong stress that induces elongation through the so-called plastic flow, before rupture, and thus separation occurs (Fig.…”
Section: The End Of a Dream: Low-temperature Embedding Of Conventionasupporting
confidence: 90%
See 1 more Smart Citation
“…With this new resin, the effects of surface relief on imaging were strongly enhanced (Kellenberger et al, 1986) and convincingly revealed the origin of the blurring. We could demonstrate a strong deformation of the resin surface in the near neighborhood of biological material, which was in full agreement with the physics of cleavage mentioned above and discussed elsewhere (Acetarin et al, 1987). Through cleavage, all matter of the section surface is submitted to strong stress that induces elongation through the so-called plastic flow, before rupture, and thus separation occurs (Fig.…”
Section: The End Of a Dream: Low-temperature Embedding Of Conventionasupporting
confidence: 90%
“…Protein fibers (e.g., hair) will have much more plastic flow than embedding resins and, therefore, emerge on both corresponding surfaces of the consecutive sections. The physics of cleavage of biological embeddings has been explained and further developed by Acetarin et al (1987). It predicts a corrugated surface, summarized in Figure 2, and we now have to demonstrate the existence and to show the consequences of this on immunolabeling and resolution.…”
Section: Relief Of Section Surface Corrugation Enables Labeling But mentioning
confidence: 81%
“…Figure 1d is a schematic drawing of the process of sectioning, which involves a complicated interplay of events: compression of the sample during the initiation of cutting, and of the slab thereafter; tension perpendicular to the plane of sectioning; generation of new surfaces; bending, as the slab reorients from vertical to horizontal; shearing stress (greatest in materials with low flexibility); friction of the slabs on the knife; and generation of heat. [55] The nascent epoxy slabs slide onto the surface of a water bath in the form of individual slabs or ribbons of connected slabs. [56] There are two general mechanisms of the process of sectioning proposed in the literature of ultramicrotomy: i) true sectioning, in which the edge of the knife maintains contact with both the bottom surface of the nascent slab and the facet of the block, and ii) crack initiation and propagation.…”
Section: Microtomy and Microscopymentioning
confidence: 99%
“…The embedding medium should have two properties, i) a relatively high value of elastic modulus (~3 GPa; materials that are too compliant deflect from the knife edge, rather than cleave), and ii) a high yield stress, only after which the material undergoes plastic deformation (~70 MPa; otherwise the slab will deform upon sectioning). [55] Crosslinked epoxy resins fill most of these criteria at ambient temperatures, although it is possible to section softer materials at cryogenic temperatures. Our laboratory has achieved excellent results with UVO-114 (Epotek), which is UV-curable, [59] and good results with Araldite 502 [60] and Epo-Fix (Electron Microscopy Sciences), [61] which are thermally curable.…”
Section: The Embedding Mediummentioning
confidence: 99%
“…Epoxy resins react with tissue elements through covalent links with the embedded tissue (Acetarin et al, 1987;Kellenberger et al, 1986;Luft, 1973). This is probably the primary reason that epoxy resins are such good glues, that they inhibit reactive sites of tissue elements, and that they give such good tissue preservation.…”
Section: Time (T) To Reach Equilibrium (E)mentioning
confidence: 99%